1987
DOI: 10.1139/v87-071
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetic exchange in poly-bis(pyrazine)bis(methanesulfonato-O)-copper(II). One-dimensional exchange in a two-dimensional polymer

Abstract: . Can. J. Chem. 65,420 (1987).Crystals of poly-bis(pyrazine)bis(methanesulfonato-O)copper(II) are orthorhombic, a = 8.199(1), b = 13.130(1), c = 6.913(1) A, Z = 2, space group Pnnm. The structure was solved by conventional heavy atom methods and was refined by full-matrix least-squares procedures to R = 0.025 and R,, = 0.033 for 1226 reflections with I 2 3u(I). The complex contains parallel sheets, each sheet consisting of a square array of copper(I1) ions bridged by two types of bidentate pyrazine ligands. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
24
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 10 publications
(13 reference statements)
3
24
0
Order By: Relevance
“…In summary, the spectroscopic studies have shown that all the compounds under consideration here are pseudo-octahedral complexes of high-spin iron(I1). The bis(pyrazine) complexes contain bridging pyrazine ligands and unidentate anions, with structures very probably similar to that of C U (~~Z )~( C H~S O~) (20) in which metal ions are bridged in a square array by neutral ligands and anions occupy transIaxial he sulfonate anions in the bis(pyridine) and the three mono(pyrazine) complexes are coordinated in a bidentate fashion yielding chromophores of the type FeN204. Although it is possible the anions are coordinated in a chelating fashion, this is considered unlikely given the strain that accompanies four membered chelate rings.…”
Section: Compound (K) (Mm S-i) (Mm S-i) (Mm S-i) (Mm S-i)mentioning
confidence: 97%
See 1 more Smart Citation
“…In summary, the spectroscopic studies have shown that all the compounds under consideration here are pseudo-octahedral complexes of high-spin iron(I1). The bis(pyrazine) complexes contain bridging pyrazine ligands and unidentate anions, with structures very probably similar to that of C U (~~Z )~( C H~S O~) (20) in which metal ions are bridged in a square array by neutral ligands and anions occupy transIaxial he sulfonate anions in the bis(pyridine) and the three mono(pyrazine) complexes are coordinated in a bidentate fashion yielding chromophores of the type FeN204. Although it is possible the anions are coordinated in a chelating fashion, this is considered unlikely given the strain that accompanies four membered chelate rings.…”
Section: Compound (K) (Mm S-i) (Mm S-i) (Mm S-i) (Mm S-i)mentioning
confidence: 97%
“…Such band splitting is not uncommon in pyrazine complexes and it has been suggested that it may arise from interactions between adjacent pyrazine rings or from different orientations of pyrazine rings giving rise to slightly different environments (2). It seems doubtful the splitting arises from significantly different structural environments for pyrazine rings as occurs in, for example, C U ( P Y Z )~( C H~S O~)~ (20). In this complex bridging pyrazine groups are of two types, one occupying equatorial positions and the other axial positions in the copper coordination sphere.…”
Section: Compound (K) (Mm S-i) (Mm S-i) (Mm S-i) (Mm S-i)mentioning
confidence: 99%
“…In contrast, the third one connects two Cu(3) ions from both axial and equatorial sites, as shown in Figure 1. As a result, the one-dimensional coordination framework composed of [-{Cu (1) 9 In this reaction, two starting [Cu(PF 6 ) 2 (py) 4 ] units dimerize with the removal of weakly coordinated PF 6 -anions and some py ligands and with an attack by MeOH molecules and MeO -anions. The dinuclear structure of 2 is shown in Figure 2.…”
mentioning
confidence: 99%
“…10 Each Cu atom shows a square-pyramidal coordination, with the basal plane formed by two N atoms of py (Cu-N = 2.000 (2) , which has a similar dinuclear structure except for the axial ligands. 8a,11 To compensate the charge balance, there are coordination-free PF 6 -anions in 2.…”
mentioning
confidence: 99%
See 1 more Smart Citation